Białoruś i Polska dwadzieścia lat w stosunkach międzynarodowych: stan obecny i perspektywy - Fedorowicz, Krzysztof (Instytut Europy Środkowo-Wschodniej w Lublinie, 2012)
An element which should be analysed was the underestimation by Poland of the fears of Belarus concerning Polonisation and the activities of the Catholic Church. Initially, issues which were of slight importance to Poland later became the main reason for serious divergences in bilateral understanding. Also of importance is the question of the awareness on the Polish side of the change in the geopolitical future of Belarus following Poland’s accession to NATO. Political changes in Belarus in the years 1994-1996 were analysed in this work as well as their influence on the deterioration of mutual relations. It was also important to answer the question about the reasons for the ineffectiveness of the policy of critical dialogue with Belarus and the causes of the conflict concerning the Polish minority in 2005.
Belarus and Poland Twenty Years in International Relations: Current Status and Prospects
Keywords: Polska; Białoruś